Slip Effects on MHD Convective Two-Phase Particulate Suspension Flow in a Convergent Channel - Ramprasad, S.; H.C.V.Subba Bhatta, S.; Mallikarjuna, B. (International Journal of Engineering and Technology, 2018)
In this article an attempt has been made to dscuss the velocity and temperature slip effects on MHD convective two phase particulate suspension flow in a convergent channel with viscous dissipation .The non dimensionalised governing equations are solved using Runge-Kutta shooting method.The results obtained are represented graphically for various emerging parameters.The skin friction coefficient and Nusselt number are obtained and validated with existing results.It is found that with an increase in velocity slip parameter the velocity of the fluid increases.The fluid phase temperature decreases with an increase in temperature slip parameter.Â